Penatalaksanaan Holistik Pasien Wanita Usia 18 Tahun dengan Asma Bronkial Melalui Pendekatan Dokter Keluarga di Wilayah Puskesmas Satelit - Jihan Nur Pratiwi; Azelia Nusadewiarti (Medula, 2022)
Asthma is a chronic inflammation of the airways that causes narrowing of the airways. The prevalence of asthma in Indonesia ranks highest for the category of non-communicable diseases. Asthma is a disease that needs to be controlled to prevent exacerbations and improve the patient's quality of life. Both patients and families are expected to have the knowledge and motivation to make lifestyle modifications so that treatment goals can be achieved, so treatment is needed through a family approach. Primary data were obtained from home visits to complement family data, psychosocial data, and the environment. Secondary data obtained from medical records. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. Patient Mrs. PF is 18 years old, has the main complaint of shortness of breath since 1 day ago. Shortness of breath accompanied by wheezing and coughing, worsening especially at night and early in the morning, cold weather, and after cleaning the house. The patient was diagnosed as bronchial asthma. In this case, diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was a decrease in clinical symptoms and an increase in the knowledge of patients and their families. The diagnosis of bronchial asthma in this patient was in accordance with the theory from several guidelines and journals, it was seen that there was a change in knowledge of the patient and his family after an intervention based on Evidence-Based Medicine that was patient-centred and a family approach.